Programa de autocontrole em um laticínio da cidade de Nova Cantu-PR - Gotardo, Crislayne (2014)
The food processing industry is concern about food quality and safety, and for this purpose several tools have been adopted to prevent possible failures and contamination during manufacturing. One of the legal requirements proposed by Brazilian Ministry of Agriculture, Livestock and Supply (MAPA) to ensure the sanitary quality of foods is the development and deployment of Control Programs. The aim of this study was to propose the implementation of a Control Program in a dairy industry located in Nova Cantu city – PR, Brazil. The work began checking the non-compliances observed during mozzarella cheese production, based on the recommendations contained in Circular number 175/2005 of the MAPA. This survey showed non-compliance in the following requirements: Lighting, Water safety, pest control, cleaning and sanitation, personal practices, temperature control, equipment calibration and measurement, and laboratory analysis controls. To overcome and eliminate the nonconformities, the employees training program was developed to discuss about the importance of Control Program, and the control program documents were written according Brazilian law. In the end of this work, 28 documents of control program were described and 24 spreadsheets to record the temperature, pH, water chlorine content, equipment calibration and personal practices.